Performance Analysis of an Integrated PV/T–TEC System with a PID enabled DC–DC Boost Converter for Photovoltaic Thermal Management - Priyo Adi Sesotyo; La Ode Muhamad Idris; Taufik Dwi Cahyono; Ery Sadewa (International Journal of Engineering Continuity, 2025)
The temperature-induced efficiency loss of 0.4% to 0.5% for every °C above 25 °C alongside the inherent variability in solar irradiance, poses a critical challenge to the efficiency and stability of Photovoltaic (PV) modules. This study addresses this limitation by developing and analyzing an Integrated Photovoltaic Thermal-Thermoelectric Cooler (PV/T–TEC) system designed for robust thermal management and enhanced energy yield. The proposed system utilizes a synergistic hybrid cooling mechanism: a passive PV/T air collector for bulk heat dissipation from the PV panel's rear surface, coupled with an active Thermoelectric Cooler (TEC) for precise temperature stabilization. The electrical energy flow is managed by a DC–DC Boost Converter employing a PID controller, with a focus on input disturbance rejection, ensuring the TEC operates at an optimal, stable power point.Simulation and performance analysis demonstrate the significant advantages of this hybridized approach. The PV/T air collector was confirmed as the primary thermal component, achieving a peak heat dissipation QEmit approximately 7.5 times greater than the TEC-only configuration. This strategic pre-cooling successfully stabilizes the TEC's hot-side temperature, enabling the TEC to operate with a low operational temperature differential ∆T and resulting in an exceptionally high calculated Effective System Coefficient of Performance COP peaking at 14.5. The system maintains a stable operating point during peak solar radiation, maximizing the Net Electrical Power Gain. In conclusion, the integration of passive PV/T cooling, active TEC cooling, and a PID-enabled DC–DC Boost Converter provides an exceptionally efficient and stable solution for PV thermal management. The research strongly supports the efficacy of this hybrid system for significantly improving the overall energy efficiency and sustainability of solar energy applications.